Learning cycles for the teaching of Mathematics in higher basic education in private educational institutions in Loja - Jiménez Albán, María Mercedes (2026)
Effective mathematics instruction at the upper basic education level requires structured learning cycles that are logical and sequential, and which promote the development of a deep and meaningful understanding. This study focuses on examining the implementation of learning cycles in mathematics instruction at the upper basic education level within private educational institutions in Loja city during the 2024–2025 academic year. The study is conducted using a descriptive, non-experimental, quantitative approach. It includes a population of 14 mathematics teachers from private educational institutions in Loja city. The empirical data are gathered through a 16-item questionnaire designed to assess the application of learning cycles. The results indicate that the ACC, Kolb, and ERCA learning cycles are the most commonly integrated into mathematics instruction. In contrast, the Karplus cycle appears to be applied informally or without deliberate intent, and the Handy cycle receives minimal attention from teachers. The study concludes that learning cycles are widely incorporated into upper basic mathematics instruction; however, their implementation varies, largely due to gaps in teachers’ understanding of the models and their respective phases.